The impact of Covid-19 on Latin American Psychology: research, profession, and public policy - Gallegos de San Vicente, Miguel Omar (2022)
In this paper, we offer an in-depth analysis of relevant scientific literature and a series of critical reflections based on a narrative review of the impact that the early stages of the Covid-19 pandemic had on Latin American psychology. We performed a non-exhaustive search, selection, and analysis of different documentary sources in scientific databases, institutional repositories, and websites of national and regional psychology organizations between May 25 and 31, 2020. In particular, we consulted SciELO, Redalyc, Dialnet, and Google Scholar using the following individual key words associated to psychology: ?Coronavirus?, ?Covid-19? and ?Pandemic?. Various types of documents were retrieved for a subsequent in-depth analysis (e.g., articles, institutional documents, notes, bulletins, recommendation guides, etc.). Our review allowed us to identify three challenges for psychology in the region: (1) insertion of psychology in public policies; (2) construction of an own agenda of psychological research; (3) evaluation of practices and reorientation of professional training processes.